Impaired tissue regeneration corresponds with altered expression of developmental genes that persists in the metabolic memory state of diabetic zebrafish - Sarras, Michael P. (2013)
As previously reported by our lab streptozocin-induced Diabetes mellitus (DM) in adult zebrafish results in an impairment of tissue regeneration as monitored by caudal fin regeneration. Following streptozocin withdrawal, a recovery phase occurs to re-establish euglycemia, via pancreatic beta-cell regeneration. However, DM-associated impaired fin regeneration continues indefinitely in the metabolic memory state (MM) allowing for subsequent molecular analysis of the underlying mechanisms of MM. This study focuses on elucidating the molecular basis that explains the DM-associated impaired fin regeneration and why it persists into the MM state with the aim of better understanding MM. Using a combination of microarray analysis and bioinformatics approaches our study found that of the 14,900 transcripts analyzed, aberrant expression of 71 genes relating to tissue developmental and regeneration processes were identified in DM fish and the altered expression of these 71 genes persisted in MM fish. Key regulatory genes of major development, and signal transduction pathways were identified among this group of 71. The aberrant expression of key regulatory genes in the DM state that persist into the MM state provides a plausible explanation for how hyperglycemia induced impaired fin regeneration in the adult zebrafish DM/MM model.